Killer B Lymphocytes and Their Fas Ligand Positive Exosomes as Inducers of Immune Tolerance - Lundy, Steven K.; Klinker, Matthew W.; Fox, David A. (Frontiers in Immunology, 2015)
Induction of immune tolerance is a key process by which the immune system is educated to modulate reactions against benign stimuli such as self-antigens and commensal microbes. Understanding and harnessing the natural mechanisms of immune tolerance may become an increasingly useful strategy for treating many types of allergic and autoimmune diseases, as well as for improving the acceptance of solid organ transplants. Our laboratory and others have been interested in the natural ability of some B lymphocytes to express the death-inducing molecule Fas ligand (FasL), and their ability to kill T helper (TH) lymphocytes. We have recently shown that experimental transformation of human B cells by a non-replicative variant of Epstein-Barr virus (EBV) consistently resulted in high expression of functional FasL protein. The production and release of FasL+ exosomes that co-expressed MHC Class II molecules and had the capacity to kill antigen-specific TH cells was also observed. Several lines of evidence indicate that FasL+ B cells and FasL+MHCII+ exosomes have important roles in natural immune tolerance and have a great deal of therapeutic potential. Taken together, these findings suggest that EBV-immortalized human B lymphoblastoid cell lines could be used as cellular factories for FasL+ exosomes, which would be employed to therapeutically establish and/or regain immune tolerance toward specific antigens. The goals of this review are to summarize current knowledge of the roles of FasL+ B cells and exosomes in immune regulation, and to suggest methods of manipulating killer B cells and FasL+ exosomes for clinical purposes.